Lucid Loop: A Virtual Deep Learning Biofeedback System for Lucid Dreaming Practice - Kitson, Alexandra (Medium, 2019)
Simply put, lucid dreaming is the ultimate virtual reality. Lucid dreaming is knowing that one is dreaming while in a dream and can allow…
Keywords: LucidLoop; Riecke_2019; alex-kitson; dissemination-4generalPublic; mediaCoverage